UPAYA KEBERLANGSUNGAN HUKUM DAN PEMBANGUNAN SEBAGAI SARANA EFEKTIVITAS PELAKSANAAN ARBITRASE DI INDONESIA - Rachmadayanti, Regina; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Arbitration is an alternative method used to resolve problems that can resolve disputes between business actors. However, in terms of implementation, there are many problems both through the national and international scope. It is appropriate, the development of law in Indonesia needs to be improved. The study of writing is carried out by qualitative research methods obtained by literature research sourced from books or literature and journals that have existed and the nature of the research in a descriptive manner. In this case, the author examines the description of writing using the theory of analysis J. D. Nyhart in law and Economic Development by looking at 7 important components, namely Predictability, Procedural Capability, Codification of Goals, Education, Balance, Definition and Clarity of Status, and Accomodation. In the results of the analysis it is obtained that there is legal uncertainty in the implementation of international arbitration awards on the national scopre so that every Foreign decision always occurs intervention and this makes forein countries view arbitration in Indonesia as an unfriendly country in terms of the implementation of Arbitration. Keywords: Agreement, Dispute, Arbitration.